Impact of Prostate Health Index Results for Prediction of Biopsy Grade Reclassification During Active Surveillance. Issue 5 (5th November 2022) - Filson, Christopher P.; Zhu, Kehao; Huang, Yijian; Zheng, Yingye; Newcomb, Lisa F.; Williams, Sierra; Brooks, James D.; Carroll, Peter R.; Dash, Atreya; Ellis, William J.; Gleave, Martin E.; Liss, Michael A.; et al.
Abstract : Purpose: We assessed whether Prostate Health Index results improve prediction of grade reclassification for men on active surveillance. Methods and Materials: We identified men in Canary Prostate Active Surveillance Study with Grade Group 1 cancer. Outcome was grade reclassification to Grade Group 2+ cancer. We considered decision rules to maximize specificity with sensitivity set at 95%. We derived rules based on clinical data (R1 ) vs clinical data+Prostate Health Index (R3 ). We considered an "or"-logic rule combining clinical score and Prostate Health Index (R4 ), and a "2-step" rule using clinical data followed by risk stratification based on Prostate Health Index (R2 ). Rules were applied to a validation set, where values of R2 -R4 vs R1 for specificity and sensitivity were evaluated. Results: We included 1, 532 biopsies (n = 610 discovery; n = 922 validation) among 1, 142 men. Grade reclassification was seen in 27% of biopsies (23% discovery, 29% validation). Among the discovery set, at 95% sensitivity, R2 yielded highest specificity at 27% vs 17% for R1 . In the validation set, R3 had best performance vs R1 with Δsensitivity = −4% and Δspecificity = +6%. There was slight improvement for R3 vs R1 for confirmatory biopsy (AUC 0.745 vs R1 0.724, ΔAUC 0.021, 95% CI 0.002-0.041) but not for subsequent biopsies (ΔAUC −0.012, 95% CI −0.031-0.006). R3 did not have better discrimination vs R1 among the biopsy cohort overall (ΔAUC 0.007, 95% CI −0.007-0.020). Conclusions: Among active surveillance patients, using Prostate Health Index with clinical data modestly improved prediction of grade reclassification on confirmatory biopsy and did not improve prediction on subsequent biopsies.